(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: The research study with entitled is about the Government Policy with its State Historical Background through the effort to prevent the jobless of Timor-Leste in providing job Management opportunities in the state and foreign countries.” The objective of this research is to identify and search on the historical and economical background of the state in providing job opportunities to young people are employed in internal and foreign countries to fix their family’s economic conditions to support the state in reducing the unemployment and poverty in the country itself as a way to settle down the problems and obtain the solution. About this, the government of Timor-Leste has created a bilateral and multilateral cooperation agreement in the country through signing the mutual of understanding (MOU) with the foreign company’s organization in abroad. The economic problems and other matters are settled with the effort hard of the state’s government by providing funds to minimize and reduce the poverty and the economic problems of the living people in the state in the current day and the future. The method of this study is qualitative and quantitative mixed methods, observing, paraphrasing, and permutation in library research through collecting the facts by using online libraries, software, and hard book references. Some of the data files presented in this writing to complete this analytical research. The finding of this research is the jobless of the country are mostly employed by the government through mutual cooperation through bilateral and multilateral cooperation to reduce the unemployment in the internal country and abroad. From the total population are not finalized their studies in the school 30,7% and from the above population, 16,8% do their learning in the higher education level. Amongst the young between 14-24 years old do not access the education, unemployed, and training and it is hard for them to get the job competition. The total labor forces in 2009, there are 430,200 people in East Timor and the unemployment are 18% since 2010.